Photochromic properties of six 5-O-n-alkyl, 6′-CN substituted spironaphthoxazines - A. V. Metelitsa; J. C. Micheau; S. O. Besugliy; E. B. Gaeva; N. A. Voloshin; E. N. Voloshina; A. Samat; V. I. Minkin (International Journal of Photoenergy)
The photochromic properties of a series of six 5-O-n-alkyl, 6′ -CN substituted spironaphthoxazines has been investigated in toluene and methanol solution. The 6′ -CN and 5-O-n-alkyl substitutions lead to a bathochromic shift of the UV spectra of the closed forms. The λmax of the visible spectra of the open forms decrease with solvent polarity. Most of the photochromic parameters have been quantitatively determined. Among them, photocoloration and photobleaching quantum yields and molar absorption coefficients of the open forms have been derived from a numerical fitting of the photokinetic curves recorded under continuous monochromatic irradiation. Results show that the photo-steady-state properties are relatively independent of the 5-O-n-alkyl chain length, but are more sensitive to the size of the indolinic nitrogen substituent.